Mirada crítica al Estado Social de Derecho y la efectivización de los Derechos Humanos en Colombia: el intento de llevar la prosperidad a través del desarrollo (2016)
To talk about human rights, entails the deduction of these - human - specific subject, but with extension in their actions towards other species living and non -living *. In this context, it underlies the idea to attempt to bring prosperity through the named developed to those considered overdue and under the global model of organization and classification between developed and underdeveloped countries. with the positivización in the rule instruments of a heap of rights widely influenced by the neoliberal model, a critical regard is in here when it is born to the social state of right and the effectivity of the human rights in Colombia as the right to the health.